Konsep Ideal Lanskap Linguistik di Ibu Kota Negara Baru (Ideal Concept of Linguistic Landscape in New State Capital) - Saefu Zaman; Anis Rahmawati; Kurniawan Kurniawan (Jurusan Tadris Bahasa Indonesia, 2023)
As the center of activity and the face of the country, the new national capital (IKN) must show national identity, one of which can be demonstrated by its linguistic landscape. This study aims to project a new national capital (IKN) linguistic landscape (LL) that highlights national identity. This research is a literature study with a qualitative descriptive method. The data of this research are studies of the linguistic landscape, regulations on language use, and data on the linguistic landscape in Jakarta as a reflection of the linguistic landscape in the new IKN. The results of the study show that in order to achieve the ideal linguistic landscape of the IKN with an Indonesian identity, the linguistic landscape in the new IKN must be principled in prioritizing the Indonesian language. To support the functions of the linguistic landscape, namely information and symbolic functions, foreign languages and/or regional languages can be used to accompany or clarify Indonesian. To achieve this, synergy is needed between the government, public area managers, and business actors. The implication of applying the ideal concept of a linguistic landscape in IKN is the establishment of the IKN area which is a symbol of the state and has an Indonesian identity.Sebagai pusat kegiatan dan wajah negara, ibu kota negara (IKN) baru harus memperlihatkan identitas kenegaraan, yang salah satunya bisa ditunjukkan dengan lanskap linguistiknya. Penelitian ini bertujuan untuk memproyeksikan lanskap linguistik (LL) ibu kota negara (IKN) baru yang menonjolkan identitas nasional. Penelitian ini merupakan penelitian pustaka dengan metode deskriptif kualitatif. Data penelitian ini adalah kajian-kajian lanskap linguistik, regulasi penggunaan bahasa, dan data lanskap linguistik di Jakarta sebagai refleksi lanskap linguistik di IKN baru. Hasil penelitian menunjukkan bahwa untuk mencapai lanskap linguistik ideal IKN yang beridentitas keindonesiaan, lanskap linguistik di IKN baru harus berprinsip pada pengutamaan bahasa Indonesia. Untuk menunjang fungsi lanskap linguistik yakni fungsi informasi dan simbolik, bahasa asing dan/atau bahasa daerah dapat digunakan untuk mendampingi atau memperjelas bahasa Indonesia. Untuk mencapai hal tersebut, diperlukan sinergisitas antara pemerintah, pengelola kawasan publik, dan para pelaku usaha. Implikasi penerapan konsep ideal lanskap linguistik di IKN adalah terbangunnya kawasan IKN yang menjadi simbol negara dan beridentitas keindonesiaan.